Distinct origin of Claudin7 in early tumor endosomes affects exosome assembly - Kyuno, Daisuke; Bauer, Nathalie; Schnölzer, Martina; Ryschich, Eduard; Hackert, Thilo; Zöller, Margot (International journal of biological sciences, 2019)
Microvesicles are the body's most powerful intercellular communication system and cancer-initiating cell microvesicles (CIC-TEX) reprogram Non-CIC towards fortified malignancy. Claudin7, a CIC-biomarker in gastrointestinal tumors, is recovered in TEX. Recent evidence suggesting individual cells delivering distinct microvesicles became of particular interest for claudin7, which is part of tight junctions (TJ) and glycolipid-enriched membrane domains (GEM), GEM-located claudin7 is palmitoylated. This offered the unique possibility of exploring the contribution of a CIC marker and its origin from distinct membrane domains on CIC-TEX biogenesis and activities. Proteome and miRNA analysis of wild-type, claudin7-knockdown and a rescue with claudin7 harboring a mutated palmitoylation site (mP) of a rat pancreatic and a human colon cancer line uncovered significant, only partly overlapping contributions of palmitoylated and non-palmitoylated claudin7 to TEX composition. Palmitoylated claudin7 facilitates GEM-integrated plasma membrane and associated signaling molecule recruitment; non-palmitoylated claudin7 supports recruitment of trafficking components, proteins engaged in fatty acid metabolism and TJ proteins into TEX. Claudin7mP also assists TEX recovery of selected miRNA. Thus, distinctly located claudin7 affects CIC-TEX composition and TJ-derived cld7 might play a unique role in equipping CIC-TEX with transporters and lipid metabolism-regulating molecules, awareness of distinct TEX populations being crucial facing therapeutic translation.
Gesehen am 22.10.2019